PROMOTING ASEAN ISLAMIC BANKING INTEGRATION: PROSPECT AND INCLUSIVE FRAMEWORK - Bawana, Tate Agape; Mansor, Fadillah; Noordin, Kamaruzaman (Online Journal of Islamic Management and Finance (OJIMF), 2025)
The implementation of the ASEAN Banking Integration Framework (ABIF) seeks to integrate the system of banking across the ASEAN region. Given the prevalence of dual banking systems across ASEAN, Islamic banking has a substantial opportunity for regional integration, and facilitating cross-border banking activities is a vital policy measure to capitalize on this. This study seeks to improve the framework for integrating Islamic banking within ASEAN by systematically reviewing and meta-analyzing how the current ASEAN Banking Integration Framework (ABIF) has been implemented. The review findings will be synthesized with existing literature to perform a thematic analysis of the challenges and opportunities facing ASEAN Islamic banking integration. A total of 39 articles, sourced from WoS and Scopus-indexed journals, were used as the primary data for this review. In alignment with established scholarship, this study posits that the successful integration of Islamic banking within ASEAN is contingent upon the implementation of robust, harmonized regulatory frameworks and standardized practices, particularly with respect to Sharia compliance. Additionally, bilateral cooperation in cross-border Islamic banking can serve as a catalyst for wider Islamic banking integration in ASEAN.